EVALUASI PEMANFAATAN APLIKASI MATERNAL PERINATAL DEATH NOTIFICATION (MPDN) DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN BANDUNG TAHUN 2024 - Pamungkas, Gugum; Luthfiyani, Heni; nurhayati asih, tri; Ramdhan, Arfian Hikmat (Jurnal Sehat Masada, 2025)
Background: Based on the results of the 2020 Long Form Population Census, there was a decrease in the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) nationally. However, when compared to other ASEAN countries, Indonesia is still among the countries with the highest MMR and IMR. Maternal Perinatal Death Notification (MDPN) is a fast, structured maternal and infant death reporting application utilising the latest information technology and can be used for tactical decision-making in efforts to reduce MMR and IMR. MPDN is also an integral part of the Maternal Perinatal Surveillance & Response (AMP-SR) Audit process. The purpose of the study was to evaluate the utilisation of the MPDN application in the working area of the Bandung Regency Health Office in 2024 based on the input, process and output components. The research method is qualitative research with in-depth interviews and observations to 7 informants. Research results: input: Human resources have been socialised, MPDN management should not be assigned to one person, facilities and infrastructure are sufficient, budget is available from the Health Operational Assistance (BOK) Puskesmas for death case tracking, Team Decree needs to be updated annually. Process: study sites have been registered in MPDN, not all deaths have been notified, reporting of Autopsy Verbal (OV) and Medical Summary (RM) is incomplete and not within the specified timeframe, zero reporting has not been done every month. Output: Recap of death report has not been made and reported every month, OV and RM documents need to be hardcopy/softcopy. Conclusion: Death notification has been implemented quite well, but needs improvement in reporting death cases in MPDN so that it can be optimally utilised for AMP-SR.